The comparative efficacy of disinfectant wipes on common-use computer keyboards in a veterinary teaching hospital - Wong, Eileen K. (Can Vet J, 2020)
The efficacies of 3 disinfectant wipes at reducing bacterial contamination on keyboards in a veterinary teaching hospital were studied. Thirty common-use keyboards were randomized into “dirty” and “clean” halves. Cultures were obtained from the “dirty” halves. The “clean” halves were disinfected with a randomly assigned wipe [peroxygen (AHP)-, alcohol-, quaternary ammonium (QAC)-based] or untreated (NT) and cultured. Colony-forming units (CFU) were enumerated after 48 hours. Mean reduction in CFU was 91.5%, 65.3%, 94.9%, and 78.8% for the AHP, alcohol, QAC, and NT groups, respectively. There was a significant reduction in CFUs between the dirty and clean keyboard halves within each group but no statistically significant differences were noted between groups. The reduction in CFUs in the NT group was attributed to the mechanical action of wiping the keyboard surface for culture. The use of disinfectant wipes reduced CFUs on keyboards and may be a useful component of veterinary infection control programs.